2015
DOI: 10.1158/0008-5472.can-14-3635
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Regulate the Systemic Response to DNA Damage by a Cell Nonautonomous Mechanism

Abstract: The DNA damage response (DDR) is a comprehensive and complex network of phosphorylation-mediated signaling pathways that originates endogenously from the DNA lesion and activates intrinsic DNA repair mechanisms. Here we describe a macrophage-dependent mechanism that regulates the response to DNA damage. We demonstrate that human monocytes, by releasing macrophage-derived HB-EGF, enhance DDR in neighboring cells suffering from DNA damage. Consequently, HB-EGF-treated cells exhibit higher double-strand break (DS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…In a recent study, we demonstrated in 1-month-old mice that diethylnitrosamine (DEN)-induced DNA damage is resolved within 6 days, reflecting the efficiency of the DNA-repair mechanisms [24]. In the present study we extended this earlier observation to mice of various ages, in order to determine how age affects the extent of DSBs generation and the kinetics of the resolution.…”
Section: Introductionmentioning
confidence: 73%
“…In a recent study, we demonstrated in 1-month-old mice that diethylnitrosamine (DEN)-induced DNA damage is resolved within 6 days, reflecting the efficiency of the DNA-repair mechanisms [24]. In the present study we extended this earlier observation to mice of various ages, in order to determine how age affects the extent of DSBs generation and the kinetics of the resolution.…”
Section: Introductionmentioning
confidence: 73%
“…Myeloid cells are recruited to the liver to repair acute DNA damage . We therefore assessed expression levels of inflammatory cytokines 48 hours after an acute DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…To test the efficiency and kinetics of DNA damage repair, we induced DNA damage in mouse livers by a single injection of DEN, as previously described 6 15. We performed immunofluorescence staining to detect cells containing phosphorylated histone H2AX (γH2AX) in liver tissue sections at days 2 and 6 following DEN injection.…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemical analysis of liver tissues was performed as described previously 6 15. For more details see online supplementary methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation